2014
DOI: 10.1104/pp.114.237941
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the in Vivo Function of α-Carboxysomes and β-Carboxysomes in Two Model Cyanobacteria

Abstract: The carbon dioxide (CO 2 )-concentrating mechanism of cyanobacteria is characterized by the occurrence of Rubisco-containing microcompartments called carboxysomes within cells. The encapsulation of Rubisco allows for high-CO 2 concentrations at the site of fixation, providing an advantage in low-CO 2 environments. Cyanobacteria with Form-IA Rubisco contain a-carboxysomes, and cyanobacteria with Form-IB Rubisco contain b-carboxysomes. The two carboxysome types have arisen through convergent evolution, and a-cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 61 publications
(87 reference statements)
11
110
1
Order By: Relevance
“…WH5701, also showed no physiological changes when acclimated to different CO 2 concentrations, but some changes in gene expression were observed (Rae et al, 2011). This is not the case for all a-cyanobacteria, as some have strong physiological responses to changes in long-term CO 2 availability Whitehead et al, 2014).…”
Section: Regulation Of the Ccm By Comentioning
confidence: 93%
See 3 more Smart Citations
“…WH5701, also showed no physiological changes when acclimated to different CO 2 concentrations, but some changes in gene expression were observed (Rae et al, 2011). This is not the case for all a-cyanobacteria, as some have strong physiological responses to changes in long-term CO 2 availability Whitehead et al, 2014).…”
Section: Regulation Of the Ccm By Comentioning
confidence: 93%
“…is in the carboxysome (So et al, 2004) O, as was observed here for Prochlorococcus spp. (Maeda et al, 2002;Whitehead et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the carboxysome might maintain a pH gradient, with the cytosolic and carboxysomal pHs differing (37,52). Altering the pH in the carboxysome would influence CCM efficiency in two ways.…”
Section: S Elongatus Cyotosolic Ph Is Within the Optimal Range For Ccmmentioning
confidence: 99%